2022
DOI: 10.3390/md20040227
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Polymeric Substances Produced by the Thermophilic Cyanobacterium Gloeocapsa gelatinosa: Characterization and Assessment of Their Antioxidant and Metal-Chelating Activities

Abstract: Cyanobacteria, particularly thermophilic strains, represent an important potential source of EPSs, harboring structural complexity that predicts diverse and specific bioactive potential. The thermophilic cyanobacteria Gloeocapsa gelatinosa, isolated from a natural hot source in Ain Echfa (Tunisia), was cultivated in a cylindrical reactor, and the production of biomass and EPSs was investigated. Results revealed that the strain is amongst the most efficient EPSs producers (0.89 g L−1) and that EPSs production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…The in vitro antioxidant activity shows prodigious potentiality to be developed as an antioxidant agent, as well as a functional additive for the food industry. A similar study was previously undertaken by Gongi et al [ 82 ], in which thermophilic Gloeocapsa gelatinosa showed similar results. Thus, EPS with an improved antioxidant capacity is reported to be utilized as antioxidant food additives [ 2 ].…”
Section: Discussionsupporting
confidence: 86%
“…The in vitro antioxidant activity shows prodigious potentiality to be developed as an antioxidant agent, as well as a functional additive for the food industry. A similar study was previously undertaken by Gongi et al [ 82 ], in which thermophilic Gloeocapsa gelatinosa showed similar results. Thus, EPS with an improved antioxidant capacity is reported to be utilized as antioxidant food additives [ 2 ].…”
Section: Discussionsupporting
confidence: 86%
“…The maximum absorption spectral wavelength area was found between 200 -230 nm, which exhibits its characteristics of functional group such as ester, carbonyl, carboxyl, and amine (Figure 2). The results are in coincidence with previous studies of marine cyanobacterium, Gloeocapsa gelatinosa (20) .…”
Section: Uv -Vis Spectroscopy Analysis Of Exopolysaccharidessupporting
confidence: 92%
“…FTIR spectra of the crude EPS produced by Bacillus sp. showed two O-H stretching at 3745 cm -1 and 3274 cm -1 (3200 -3800 cm -1 range) and are the typical characteristic of a carbohydrate group similar to Gloeocapsa gelatinosa (20) . A weak Chttps://www.indjst.org/ H stretching band was absorbed in 2931 cm -1 can be attributed to the C-H stretching of methyl groups, which are typically found in hexoses such as glucose or galactose or deoxyhexoses such as rhamnose or fucose in reference to previous studies by Bacillus xiamensis (18) .…”
Section: Ftir Analysis Of Exopolysaccharidesmentioning
confidence: 97%
“…The results obtained agree with several studies that showed that polysaccharides with a net negative charge ameliorates their water solubility and activity as an ion exchange matrix of cations. In particular, polysaccharides that contains the functional groups and the characteristics mentioned above are able to reduce redox potential, stabilise the oxidation form of metal ions, prevent the production of excessive free radicals and protect the body from oxidative stress by chelating metal ions [31,32]. The analysis of monosaccharide composition of lyophilized samples revealed the presence of 11 different monosaccharide moieties, including two uronic acids and two amino sugars, as shown in Figure 4.…”
Section: Zeta Potential Of M-psmentioning
confidence: 99%